2007
DOI: 10.2105/ajph.2006.090399
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Disseminating Evidence-Based Interventions That Promote Physical Activity to Health Departments

Abstract: Our exploratory study provides several dissemination approaches that should be considered by practitioners as they seek to promote physical activity in the populations they serve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 39 publications
2
84
0
Order By: Relevance
“…The reach of these training programs can be increased by emphasizing a train-the-trainer approach (22). Other formats have been used including Internet-based self-study (101,105), CDROMs (20), distance and distributed learning networks, and targeted technical assistance. Training programs may have greater impact when delivered by change agents, who are perceived as experts yet share common characteristics and goals with trainees (137).…”
Section: Wwwannualreviewsorg • Evidence-based Public Healthmentioning
confidence: 99%
“…The reach of these training programs can be increased by emphasizing a train-the-trainer approach (22). Other formats have been used including Internet-based self-study (101,105), CDROMs (20), distance and distributed learning networks, and targeted technical assistance. Training programs may have greater impact when delivered by change agents, who are perceived as experts yet share common characteristics and goals with trainees (137).…”
Section: Wwwannualreviewsorg • Evidence-based Public Healthmentioning
confidence: 99%
“…This shows that SARC is in line with the equity principles of the Brazilian public health system 2 ; the aim of reducing inequalities is being achieved. In this context, previous studies have demonstrated that achieving long-term participation in ongoing programs is a challenge because people can modify their behavior in the long-run 3,[18][19][20] . Family commitments, diseases, motivation, injury or work can be some adherence barriers [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…The translation of systems research into practice has stimulated investigations into developing academic perspectives on translational efforts (25), evaluating the effectiveness of study designs for translation research (62), and determining the dissemination effectiveness for single-issue health promotion interventions (18,19). Although logic models for translating research to practice typically include fundamental translation activities, feedback loops, phased actions, and pilot tests (79, 97), they do not typically incorporate the context and nature of a public health system that functions largely outside the control and resources of a single agency (49).…”
Section: Wwwannualreviewsorg • Recent Advances In Phsrmentioning
confidence: 99%